Health conditions of heavy vehicle drivers involved in a crash in Western Australia: a retrospective study using linked data - Lee, Andy; Meuleners, Lynn; Legge, M.; Cercarelli, Rina (Australian Health Promotion Association, 2005)
Issue addressed:This retrospective study investigated the health conditions of a cohort of heavy vehicle drivers involved in a crash in Western Australia.Methods: Hospital separation records of heavy vehicle drivers admitted to hospital as a result of a road crash between 1 January 1988 and 31 December 2000 in Western Australia were analysed. Heavy vehicle drivers involved in a crash were first identified using the Western Australian Road Injury Database before linking to their hospital records. All hospital admissions for each driver admitted to hospital for a crash at least once during the study period were subsequently retrieved from the Health Services Linked Database.Results: There were 146 heavy vehicle drivers in the cohort. A total of 964 distinct in-patient episodes (the collection of all hospital admissions for a single event) were recorded for these drivers, with a minimum of one and a maximum of 84 hospital in-patient episodes per driver. The mean number of in-patient episodes for each driver was seven (SD=8.44), including an in-patient episode for a heavy vehicle crash.Conclusion: The evidence presented for the cohort of heavy vehicle drivers hospitalised as a result of road crash confirms that these drivers are characterised with health conditions such as musculoskeletal problems and digestive disorders.